Hepatocellular carcinoma with extrahepatic blood supply from right renal artery. Issue 10 (11th October 2021) - Sohail, Amir Humza; Musa, Ahmad; Khan, Muhammad Salman; Hashmi, Hassan Raza; Salam, Basit; Brathwaite, Collin E M
Abstract: Extrahepatic blood supply is seen in around 17–27% of hepatocellular carcinoma lesions. Evidence suggests that this extrahepatic supply most commonly originates from a right intercostal artery (70–83%) followed by left intercostal, omental and right renal arteries. Thus a comprehensive knowledge of variations in standard vascular anatomy and cognisance of factors influencing or predicting extrahepatic blood supply in HCC is instrumental in ensuring the success of surgical and interventional procedures. We present the unusual case of a 66-year-old male with HCC in Segment I of the liver with aberrant blood supply from the right renal artery in the absence of any risk factors for extrahepatic circulation. He successfully underwent transarterial chemoembolization. There was no evidence of residual disease on repeat imaging.